We Are Concerned about the Future and We Are Here to Support the Change: Let's Talk and Work Together! - Cátia Branquinho; Luís Lobo Xavier; Catarina Andrade; Tomás Ferreira; Catarina Noronha; Tony Wainwright; Margarida Gaspar de Matos (MDPI AG, 2022)
Scarcely explored, intergenerational dialogue may support the re-encounter between generations. Background: Focused on intergenerational sharing and on the identification of differences between generations, the project #GenerationsWithAVoice aims to identify generational inequalities, with the aim of promoting awareness of intergenerational challenges, boosting public debate and interest in public policies. Methods: Twenty focus groups were developed, and an evaluation instrument was applied. Results: (i) Young people believe that they have more knowledge, but less propensity for action, leaving this task to the following generations; (ii) the family and housing emerge as the issues with the greatest number of problems identified, but also as important resources; (iii) government and politics, community and society, and the economy are of less interest and knowledge on the part of this generation; (iv) school seems to be the ideal scenario for the implementation of strategies that lead to change. Conclusions: We highlight the role of this work in the deconstruction of beliefs regarding previous generations, the development of knowledge, and the promotion of cohesion and social support.